Depression and coping strategies used among adolescents with cystic fibrosis - Tiwari, Surya Kant; Sharma, Rimple; Joshi, Poonam; Kabra, Sushil Kumar (International Journal of Contemporary Pediatrics, 2021)
Background: Cystic fibrosis (CF), an autosomal recessive monogenic chronic disorder affects the lungs, pancreas, and other exocrine glands, and manifests as recurrent respiratory infections, malabsorption, and a myriad of complications pertaining to other systems like hepatobiliary, endocrine and reproductive systems. Objectives were to assess the level of depression among adolescents with CF, to assess the coping strategies used by adolescents with CF and to find an association between selected sociodemographic and clinical variables with depression. Methods: In a cross-sectional survey, 30 adolescents with CF in the age group of 12-18 years, attending the specialty clinic of a selected tertiary care facility were enrolled using a purposive sampling technique. Tools consisting of sociodemographic and clinical profile, patient health questionnaire (PHQ)-9, and ways of coping with CF were used for data collection. Results: Most of the adolescents with CF (66.7%) had depression of varying severity with 36.7% having moderate-severe to severe depression. The frequently used coping strategies by the adolescents with CF were hopefulness (76.66±11.29), followed by optimistic acceptance (70.23±13.04). The individual coping strategy with the highest mean score was “having confidence on doctor and treatment” (3.83±0.37), while ‘I cry, eat, drink or take drugs’ had the lowest score (1.6±1.00). Conclusion: Depression is a common problem among adolescents with CF requiring regular screening and referral to experts for enhancing their coping strategy of optimistic acceptance.